INFLUENCE OF WHEY FOLIAR SPRAYING AND GROWING POINT PINCHING ON GROWTH AND YIELD PARAMETERES OF OKRA - & Muhammed, Abed AL-Hussain (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
An experiment was carried out in the fields that belong to agiriculture college /Baghdad university (AL-Jadyria) according to randomized compeleted blocks design(R.C.B.D.) with three replications during the spring season of 2015 to Study impact of growing point pinching and foliar spraying of whey on some traits of vegetative growth and yield of okra(Abelmoschus esculentus L.Moench) AL-Batra local cultivar.The experiment was included six treatments which was pinching or no pinching of growthing point and foliar spraying of whey with three concentration (0%,50%and75%).The results showed that pinching was siginificant in all traits of vegetative growth except plant High where the highest values of branches number , diameter of stem and leafes numbers which were(1.911 branch/plant , 3.45 cm/plant ,84.0 leaf/plant) respectively while there was not significant differences in foliar spraying of whey in all traits except plant high which was(163.6 cm/plant)with 75%. The interaction between pinching and foliar spraying of whey with(75%)was significant to plant high and branches number which were (167.0 cm/plant and 2.133 branch/plant) respectively and the interaction between pinching and comparison treatment of whey(0%) was significant to diameter of stem and leafes number which were (3.67 cm/plant and 88.80 leaf/plant) respectively. The results point out that pinching treatments were not significant in all traits of yield while whey fliar spraying with(50%) was significant to fruit weight average and yield per plant which were (2.76 gm/plant and 0.2103 kg/plant) respectively. The interaction between pinching and comparison treatment of whey(0%) was significant to fruits number per plant which was(82.7 fruit/plant) and interaction between pinching and foliar spraying of whey with(50%) was significant to fruit weight average and yield per plant which were(2.92 gm/fruit and 0.228 kg/plant) respectively.